Prolonged activation of the coagulation system during in vitro fertilization cycles. (September 2017) - Cohen, Yoni; Tulandi, Togas; Almog, Benny; Zohav, Eyal; Deutsch, Varda; Many, Ariel; Amit, Ami; Cohen, Aviad
Abstract: Objective: To investigate coagulation system changes during an in-vitro fertilization (IVF) cycle using Thromboelastogram (TEG) that enables analysis of the elastic properties of whole blood samples and provides a global assessment of the hemostatic function. Study design: A prospective study. TEG indices were evaluated in 23 women who underwent controlled ovarian stimulation for IVF at four points in time: 1. At the beginning of the cycle (corresponding to the lowest levels of E2), 2. On the day of hCG administration (maximal stimulation with highest E2 levels), 3. On the day of ovum pickup and 4. At the first pregnancy test (approximately 14 days after ovum pickup). The main outcome measures were TEG indices including R-time (time until initial fibrin formation), K-time (time until a 20 mm amplitude is achieved), α angle (the rate of clot formation), Maximum Amplitude (MA, strength of the fibrin clot), Coagulation Index (CI, calculated overall indicator of coagulation) and LY30 (the decrease in graph amplitude). Results: R, K, α angle, MA and CI before hCG administration and at the time of the first pregnancy test were significantly higher compared to the baseline measurement before gonadotropins administration. No correlation was found between E2 and TEG indices. Conclusion: Ovarian stimulation is associated with prolonged increased coagulability that extends after the time of maximal ovarian stimulation. The lack of association between E2 levels and TEG indices suggest that additional factors may play a role in the pathogenesis of increased coagulability in women with ovarian stimulation.